SEASONAL FEATURE OF THE HYDROLOGY OF THE BALI STRAIT - Ilahude, Abdul Gani (Marine Research in Indonesia, 1975)
Using the data in the file of the Lembaga Oseanologi Nasional (LON = National Institute of Oceanology), Jakarta, it is shown that the hydrological features at the surface of the Bali Strait are closely related to the meteorological factors of the region. Furthermore, based on the data obtained from the four oceanographical cruises organized by LON in the strait, the features at subsurface layer are analyzed. The influence of the current system south of Java and the upwelling associated with it are also discussed.